Pendugaan Umur Simpan Bubuk Daun Torbangun Dalam Berbagai Jenis Kemasan - Ariani, Lydia; Hasbullah, Rokhani; Ahmad, Usman (Jurnal Keteknikan Pertanian, 2021)
Torbangun leaf powder can improve the quality and quantity of breast milk in pregnant and lactating women because it contains bioactive compounds from phenol group, especially thymol and carvacrol. The purpose of this study was to examine parameters change of torbangun leaf powder (moisture content, free fatty acids, antioxidant activity and total phenol), and estimate shelf life of torbangun leaf powder in various packaging. Accelerated Shelf-Life Testing method based on Arrhenius approach was used to estimate shelf life of torbangun leaf powder. 100 g of torbangun leaf powder were stored in three packaging materials, namely HDPE, PP and aluminum foil at 30oC, 35oC, 40oC, 45oC and 50oC. The results showed that temperatures affect moisture content, free fatty acids, antioxidant activity and total phenol of torbangun leaf powder. Arrhenius model describes total phenol change, where ln k= 28.29 × -9746.8/T, ln k= 30,866 × -10565/T and ln k= 29,162 × -10019/T for HDPE, PP and aluminum packaging. foil. Thus, shelf life of torbangun leaf powder at 15oC and 28oC for HDPE is 691 days and 160 days, followed by PP is 899 days and 184 days, and aluminium foil is 807 days and 173 days.